Morphofunctional Characteristics of Basketball Players with Different Roles as Selection Criteria at the Stage of Preparation for Higher Achievements - Mykola Bezmylov; Oksana Shynkaruk; Nataliia Byshevets; Gan Qi; Shao Zhigong (OVS LLC, 2022)
Objective. To study the morphofunctional characteristics of basketball players aged 17-20 years, taking into account their game role, and to substantiate the possibility of using them as criteria for selection and orientation at the stage of preparation for higher achievements.  Materials and methods. The study participants were 200 basketball players (17-20 years old). The following methods were used: theoretical analysis, pedagogical observation, pedagogical experiment with the use of instrumental methods of functional diagnostics (ergometry, chronometry, spirometry, gas analysis, and pulsometry), anthropometric methods, statistical methods.  Results. The study determined statistically significant differences in height and weight in all playing positions: the point guard is characterized by statistically significantly shorter body height compared to the shooting guard (U = 46.5; z = -6.88; p < 0.01), the shooting guard is statistically significantly shorter than the small forward (U = 51.0; z = -5.58; p < 0.01), the latter is shorter compared to the power forward (U = 38.0; z = -5.56; p < 0.01). The center was found to be statistically significantly taller than the power forward (U = 82.0; z = 4.24; p < 0.01). The model height indicators of centers at this stage of improvement are 205.9 ± 3.53 cm. Groups of athletes, depending on their roles, statistically significantly differ in body weight (F = 64.304; p < 0.01). Centers are the heaviest and point guards - the lightest basketball players. The dynamics of body height and weight indicators of basketball players from 16 to 20 years were determined. Point guards and shooting guards have a statistically significantly higher level of VO2max compared to centers and power forwards. The average level of VO2max of players in the point guard position was 57.05 ± 3.78 ml.kg.-1min. In centers, this indicator is on average 49.10 ± 4.63 ml.kg-1.min-1. Centers had the VLC in the range of 9.38 ± 0.76 l, power forwards - 8.72 ± 0.80 l, defensive players - 7.5-8 l. No statistically significant differences were found in players with different roles in the level of AnT as a percentage of VO2max. Conclusions. Morphological and functional characteristics serve as informative criteria for monitoring the individual condition of players, are dynamic and can be used in different age groups, taking into account the specifics of team training and individual qualities.